Self-recognition in a young chimpanzee - Muhamad, Azim Salahuddin (2016)
Animal cognition refers to the mental capabilities and the memory of an animal. The cognitive function also provides the evidence of self-awareness, which describe as to distinct of oneself as an individual separate from the environment and other individuals. The mirror self-recognition (MSR) test or mark test is a behavioural technique introduced by psychologist, Gallup, G. in 1970s which to determine whether non-human possess the ability of self-recognition. Therefore, the objective of this study is to measure and analyse the self-recognition of a young chimpanzee. Animal was selected (n=1; Pan troglodytes) from Zoo Negara Malaysia and the acrylic mirror (60x84cm: A1 size) was placed outside of the cage. The animal also was marked with odourless non-toxic white paint for MSR test. Open mirror and mark test behaviour were recorded using a video camera for a week and all data were analysed using the ethogram procedure. Theoretically, animal that are considered to be able to recognize themselves in a mirror typically through four stages of behaviour such as social responses, physical inspection, repetitive behaviour and realization of seeing themselves. Result showed that the animal has positive MSR in an open mirror test. However, the animal does not show self-recognition towards the mark, which indicates to negative MSR. Several factors such as bar cage, insufficient lighting, and reduce in mark colour may cause the animal not to act towards the mark. Therefore, further research is needed to understand the real capability of the chimpanzee in recognising itself. The understanding of cognitive ability as an effort to help the animals such as management and in program to re-establish populations of endangered or threatened species.